2019
DOI: 10.3389/fneur.2019.00354
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive Craniectomy for Traumatic Brain Injury: Postoperative TCD Cerebral Hemodynamic Evaluation

Abstract: Background: There are no studies describing the cerebral hemodynamic patterns that can occur in traumatic brain injury (TBI) patients following decompressive craniectomy (DC). Such data have potentially clinical importance for guiding the treatment. The objective of this study was to investigate the postoperative cerebral hemodynamic patterns, using transcranial Doppler (TCD) ultrasonography, in patients who underwent DC. The relationship between the cerebral circulatory patterns and the patients' o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Patients submitted to DC have a more severe neurological condition, and that is the reason why the ICP was higher and the P2/P1 ratio remained higher after DC in comparison to other groups. Interestingly, despite the higher ICP values, our study demonstrated greater ICC in this group as observed with the P2/P1 ratio after an induced rise in ICP [23,24]. This phenomenon has never been demonstrated before and should be further explored as an indicator of successful DC.…”
Section: Discussionsupporting
confidence: 47%
“…Patients submitted to DC have a more severe neurological condition, and that is the reason why the ICP was higher and the P2/P1 ratio remained higher after DC in comparison to other groups. Interestingly, despite the higher ICP values, our study demonstrated greater ICC in this group as observed with the P2/P1 ratio after an induced rise in ICP [23,24]. This phenomenon has never been demonstrated before and should be further explored as an indicator of successful DC.…”
Section: Discussionsupporting
confidence: 47%
“…• Sites of dural insertion. Although literature [40] has defined "hyperemia" with MCA MFV >100 cm/s, there is an increase in MCA MFV >30% in comparison with pre-DC values. Turbulent flow, vascular congestion, increasing spectral Doppler waveform amplitude and a marked decrease in PI are also shown, which suggests a possible "exacerbated" reperfusion phenomena of the vascular territories secondary to intracranial pressure reduction after DC.…”
Section: Closed Box Open Boxmentioning
confidence: 92%
“…Understanding the different cerebral hemodynamic patterns (pre-and post-DC), help the implementation of timely therapeutic decisions individualized to optimize CPP for each patient. Therefore, keep in mind that generalized treatment goals [17] can lead to hypo-or hyperperfusion phenomena, being deleterious for the patient [11,12,39,40] (Figs. 55.4a-c and 55.5).…”
Section: Tcd/tccs: Hemodynamic Changes Associated With Decompressive Craniectomymentioning
confidence: 99%
“…The most common difference after decompressive craniectomy is an asymmetrical increase in cerebral blood flow velocities with a higher increase in the decompressed side than the opposite side. A decrease in the pulsatility index has also been reported [19][20][21]. Monitoring the decompressed patient with transcranial Doppler ultrasound is remarkably important as different hemodynamic patterns have been described after the procedure.…”
Section: Decompressive Craniectomymentioning
confidence: 94%